2007
DOI: 10.1007/s00405-007-0422-x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent facial nerve paralysis: an unusual presentation of fibrous dysplasia of the temporal bone

Abstract: Facial nerve paralysis (FNP) is a rare occurrence in fibrous dysplasia (FD) of the temporal bone (FDTB). Eight such cases have been described in the literature. In none of these cases was the FNP the presenting symptom, and in all, a direct etiology for the paralysis was identified. We present the first case of recurrent, unilateral FNP as the sole otological manifestation of FDTB. We discuss possible etiological factors for the paralysis favoring a compressive, transient ischemia of the facial nerve. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…In a review of the literature, Megerian et al identified four cases (10%) of facial nerve paralysis: two with concurrent acute otitis media and two with progressive long‐standing paralysis ascribable to fallopian canal impingement. Since that time, only a few additional cases have been reported in the literature . Because radiologic impingement of the fallopian canal is common, but facial nerve palsy is very rare, it seems clear that prophylactic cranial nerve decompression is unwarranted in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature, Megerian et al identified four cases (10%) of facial nerve paralysis: two with concurrent acute otitis media and two with progressive long‐standing paralysis ascribable to fallopian canal impingement. Since that time, only a few additional cases have been reported in the literature . Because radiologic impingement of the fallopian canal is common, but facial nerve palsy is very rare, it seems clear that prophylactic cranial nerve decompression is unwarranted in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is quite rare and is likely caused by the compression of the cranial nerve within the Fallopian canal and/or the internal auditory canal [71,83,86,87]. Unfortunately, the location of the compression may be extremely difficult to access.…”
Section: Auditory Canal/temporal Bone/cranial Nervesmentioning
confidence: 99%
“…La sintomatología primordial cuando afecta el hueso temporal es pérdida auditiva en el 80% de casos, siendo la más común la de tipo conductiva (79%), causada por oclusión de la trompa de Eustaquio, del conducto auditivo externo o erosión de la cadena osicular 15 . La pérdida sensorineural se presenta en el 14%-17% de los pacientes 1,6 , siendo secundaria a fístula laberíntica por colesteatoma o estenosis de conducto auditivo interno 16 .…”
Section: Discussionunclassified
“…Las complicaciones de la enfermedad incluyen otitis externa recurrente, formación de colesteatoma la mayoría en canal auditivo externo (40%), erosión de los huesecillos, alteraciones en la cápsula ótica, fistulización y laberintitis del canal semicircular lateral; parálisis facial en el 10% de casos (15) , casi todos en variante monostótica y secundaria a compresión o destrucción del nervio en el canal de Falopio, o por estrechamiento del canal auditivo interno asociado con alteración de otros nervios craneales 1,15 (Tabla 2).…”
Section: Discussionunclassified